Expert psychological assessment of psychological damage or affectation in women victims of violence: a characterization of current practices in Ecuador - Francis Bone, Mónica Alexandra (2023)
Due to detected issues in Ecuadorian practices on the forensic psychological assessment of psychological damage or effects on women victims of violence, this paper aims to characterize the forensic psychological assessment carried out to date from those professionals’ perspectives. It allows the authors to define indicators for improving those psychological practices. The data were gathered by applying a validated questionnaire supported on Google Forms to a sample of thirty-one professionals from the public and private sectors. Regarding the current practices carried out by those professionals, the authors conclude there is a trend of lacking knowledge on its legal and ethical foundations and did not follow a theoretical-methodological model as a guide, while the psychological tests used limit the approach to a complex phenomenon such as violence. However, they recognize the need to improve their practices. Based on these findings, limited by the number of participants, there is a need to strengthen forensic psychologists’ practices, both in theoretical-methodological and ethical issues, looking at indicators and tools that allow professionals to improve their forensic work. In this sense, a Procedures Manual could fill this gap.